Caracterização dos efeitos da exposição materna ao Triclosan, durante a prenhez e lactação, na morfofisiologia uterina da prole feminina de rato - Bitencourt, Guilherme (2018)
Triclosan (TCS) is an antimicrobial agent widely used in manufactured products, especially in personal care and oral hygiene products. Studies prove that it changes the homeostasis of several organisms and is therefore considered an endocrine disruptor. Thus, the aim of the present study was to evaluate the effects of maternal exposure to TCS during pregnancy and lactation in the uterine morphology of the rat offspring. For this, thirty-two pregnant rats were divided into 4 groups of 8, treated once daily orally, during pregnancy and lactation, as follows: Group I - control (GI): corn oil; Group II (GII): TCS diluted in corn oil at a dose of 75 mg/kg/day; Group III (GIII): TCS diluted in corn oil at a dose of 150 mg/kg/day; Group IV (GIV): TCS diluted in corn oil at a dose of 300 mg/kg/day. A female cub of each mother was selected, and at 90 days the pups were euthanized for weighing and collection of the uterus for histomorphometric analysis. The results showed that the mean litter weight was minor in all the groups treated with TCS, when compared to control. The offspring of all groups exposed to TCS presented estrous cycle dysregulation, compared to control. Analysis of the uterine histological structure demonstrated that all layers of the uterus were affected by the administration of TCS, and the morphometric analysis showed increased uterine layers in the treated groups. The leukocyte count showed an increase in inflammatory infiltrate in the groups of 150 and 300 mg of TCS, in comparison to the other groups. It is concluded that maternal exposure to TCS, during pregnancy and lactation, causes a decrease in the mean weight of the litter, deregulates the estrous cycle and causes a change in the uterine structure of the offspring.